2020
DOI: 10.1186/s12913-020-05903-1
|View full text |Cite
|
Sign up to set email alerts
|

Incident reports involving hospital administrative staff: analysis of data from the Japan Council for Quality Health care nationwide database

Abstract: Background Task shifting and task sharing in health care are rapidly becoming more common as the shortage of physicians increases. However, research has not yet examined the changing roles of hospital administrative staff. This study clarified: (1) the adverse incidents caused by hospital administrative staff, and the direct and indirect impact of these incidents on patient care; and (2) the incidents that directly involved hospital administrative staff. Methods This study used case report data from the Japan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…We are not aware of the reasons for the small number of non-medical incident reports. However, a previous study using the JCQHC data reported that the number of reports from hospital administrative staff was small, and this trend was similar between hospitals [ 16 ]. Incident reporting research has focused on medical staff, such as physicians, nurses, and pharmacists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are not aware of the reasons for the small number of non-medical incident reports. However, a previous study using the JCQHC data reported that the number of reports from hospital administrative staff was small, and this trend was similar between hospitals [ 16 ]. Incident reporting research has focused on medical staff, such as physicians, nurses, and pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was conducted by two researchers with a registered nurse qualification, one of whom also had a patient safety qualification and experience in content analysis. Textual data were analysed focusing on factors regarding the “what” and “why” of the reported incident, according to a previous study [ 16 ]. The two researchers analysed the data independently and then compared the identified contents to cross-check their validity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the use of personal protective equipment is very important in the prevention of work accidents. Work accidents can happen to every worker in doing work, because a work accident is an event or event that is undesirable to humans, damages property, or losses to the process in a job (Akiyama et al, 2020).…”
Section: Benefits Of Using Personal Protective Equipmentmentioning
confidence: 99%
“…Safety incidents that occur only at the beginner level are not done at the advanced level. The implications of this study are important as a reference to develop a new education system for nursing training in the workplace (Akiyama et al, 2020).…”
Section: Introductionmentioning
confidence: 95%